MENINGKATKAN KESADARAN REMAJA TENTANG BAHAYA PERNIKAHAN DINI MELALUI PENDEKATAN BIMBINGAN ISLAMI DI MTs SWASTA WABURENSE BUTON TENGAH - Edison; Samsaifil; Bin Anuar, Arman; Yungmi (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The high rate of early marriage in Terapung Village, Central Buton Regency, is a serious concern in efforts to improve the quality of life of adolescents and break the cycle of poverty and unpreparedness for family. This Community Service (PkM) activity was carried out at MTs Swasta Waburense with an Islamic guidance approach as the main strategy to improve students' understanding of the dangers of early marriage. Through a series of activities in the form of an initial survey, provision of educational materials, group discussions, and spiritual guidance, students were invited to understand the importance of physical, mental, and moral responsibility readiness before entering marriage. The results of the activity showed a significant increase in students' awareness and attitudes towards the risks of early marriage, as well as a growing commitment to continue their education and postpone marriage until they were truly ready. The Islamic guidance approach has proven effective in touching on students' cognitive and emotional aspects, as well as strengthening spiritual values ​​as a basis for decision making. This activity received full support from the school and community, and is recommended to be adopted sustainably as part of the local curriculum and policy in efforts to prevent early marriage among adolescents.